Effect Analysis of e-Catalog Implementation on Income Increase Through Accounting Information System (SIA) Sales SMEs Batik Tulis - Mardiana Andarwati; Edi Subiyantoro; Tutut Subadyo (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2018)
Increased profit of batik SMEs is influenced by the use of e-catalogs and profits is increasing if e-catalogs also apply sales SIA. This study aims to (1) analyze the effect of application of batik e-catalog on sales SIA, (2) to analyze the effect of the application of batik e-catalog on increasing the profit of batik SMEs; and (3) to analyze the effect of the application of e-catalog of batik to increase the profit of SMEs batik tulis through SIA sales. The results of research is increasing profit if e-catalog is applied because the consumer network is increasingly widespread and profit is increasing if supported by the SIA integrated sales means consumers choose batik tulis in e-catalog and then make sales transactions through SIA online sales so much easier for consumers buy batik products so that the impact on increasing the profit of SMEs batik tulis.